ANALISIS KESALAHAN BAHASA INGGRIS DALAM STATUS DAN OBROLAN DI MEDIA SOSIAL BBM - SUPIT, RINNI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research, entitled â€œError Analysis of English in Status and Chatting in theÂ  Social Media BBMâ€, is an attempt to identify, classify, analize and describe the kinds of errors in the use of Social Media BBM. This research gives contribution in terms of understanding the error analysis especially the errors of the BBM users in chatting and status. Ellisâ€™s theory is used to analyze the errors in the Social Media BBM. The result of this research shows that there are 16 kinds of errors made by BBM users, they are omission ofÂ  the subject, omission ofÂ  verb (to be),Â  omission of the ending for plural nouns, omission of a preposition, omission of auxialiary verb (to be, to do and to have) and omission of an article. Errors of misinformation are misinformation of singular nouns, misinformation of plural nouns, misinformation of subject, misinformation of object, misinformation of preposition, misinformation of verb and misinformation of word spelling. Errors of misordering are misordering of object, misordering of adverb ofÂ  place and misordering of adverb of time. Keywords: error analysis, Status and Chatting Social Media BBM